Analisis Pengaruh Kualitas Layanan terhadap Kepuasan dan Loyalitas Mahasiswa di Universitas AMIKOM Yogyakarta - Fatima Indah Hayati; Zuprizal Zuprizal; Singgih Hawibowo; Yusuf Amri Amrullah (MANAZHIM, 2021)
This research aims to know the influence of quality service toward the students’ satisfaction and loyalty at AMIKOM Yogyakarta University. Research method is Quantitative Associative. The research participants of this research were 454 students who were chosen by purposive sampling technique. This research used a questionnaire that contained 41 questions. The result of this research was analyzed using Structural Equation Modeling (SEM) with the help of smartPLS v.3.2.8 program. The result of the analysis process showed: (1) Quality service had a significant and positive effect on the students’ satisfaction with coefficient value of path analysis was 0.566. T statistic was 12.737 and the p-value was 0.000. Self Development Opportunity Dimension was the dimension which had the biggest influence toward the students’ satisfaction, and internationalization dimension has the smallest influence toward the students’ satisfaction, (2) Quality service had a significant and positive effect toward the students’ loyalty with coefficient value of path analysis was 0.242, T statistic was 4.834 and the p-value was 0.000. Self Development Opportunity Dimension was the dimension which had the biggest influence toward the students’ satisfaction, and internationalization dimension has the smallest influence toward the students’ satisfaction, (3) The students’ satisfaction had significant and positive effect toward the students’ loyalty with coefficient value of path analysis was 0.,516. T statistic was 10.919 and p-value was 0.000, (4) Students’ satisfaction is partial mediation of the influence of quality service toward the students’ loyalty with total effect value was 0,534.